Virtual learning due to covid-19 pandemic and body weight changes in children aged 6-12 years - Aulia, Nadhira Haliza; Santoso, Andintia Aisyah; Ramadhanty, Mutiara; Wirawan, Bintang; Soesanti, Frida (Paediatrica Indonesiana, 2024)
Background The COVID-19 pandemic has led to school closures and virtual learning implementation. The situation has affected children's lifestyles and created an obesogenic environment. Objective To evaluate the impact of virtual learning during the pandemic on body weight changes in children. Methods This cross-sectional study was conducted on 6-12 years age children who experienced virtual school learning in Jakarta, Indonesia. Parents or guardians were asked to complete an online questionnaire about lifestyle changes and children's anthropometric data both before and during the virtual learning period. Changes in the weight-for-age Z-score (WAZ) and BMI Z-score (BMIZ) were analyzed using the Wilcoxon signed-rank test. Results A total of 206 children were assessed. There was a significant relation between virtual learning due to the COVID-19 pandemic and WAZ and BMIZ changes among children aged 6-12 years. Approximately 64% of the children experienced WAZ decrement (P value = 0.000), and 77.1% experienced BMIZ decrement (P value = 0.000). Conclusion This study do not align with existing studies' indicating that the pandemic lead to weight gain in children. Instead, the results shows that virtual learning period causes both WAZ and BMIZ to decrease.